THE CORRELATION OF LIFE SKILLS EDUCATION RESULT TOWARD IMPROVEMENT OF PUBLIC WELFARE IN INBASARI BEAUTY INSTITUTIONS IN THE VILLAGE OF CEMPAKABARU, CENTRAL JAKARTA - Yulastri, Lilies; Yudaningsih, Tri (Prosiding Pendidikan Teknik Boga Busana, 2020)
This research aim to determine whether there is a correlation of life skills in the areas of skills executed by the Skills and Training Institute for the public welfare This research was used survey and correlation method. The population in this study werestudents who had been trained about beauty makeup in skills and training institutions in the period from 2009 to 2011. Sampling was done by probability sampling, which is the random sampling. Total sample of 30 people. Research instrument obtained of recapitulation final value of beauty life skills education that already exist in the LKP (Expost Facto). While welfare instrument data using questionnaires. Reliable and test validity, This proves that the instrument used has a very high reliability or strong is rxy = 0,616. The results of the data analysis are as follows: The regression equation obtained is Y=-30,20+0,60 X. Test requirements derived from analysis of error estimates of regression Y on X is normally distributed (Lcalculate =0,161ttable (1,70). It is indicates that the hypothesis (Ho) is rejected, and (Ha) is accepted, it is concluded there is a positive correlation between life skills education in beauty specification to the raising of public welfare. The calculation of the coefficient of determination shows that the public welfare variation (variable Y) is determined by the educational welfare outcomes (variable X), with implications if the results of the higher education life skills that will be followed by the higher public welfare. Key Word : The correlation of life skills education result in inbasari beauty institutions in the village of cempakabaru, centraljakarta